Exercise-induced ventricular arrythmia in asymptomatic patients with Mitral Valve Prolapse. (3rd October 2022) - Wallet, T; Al Mohani, A; Waintraub, X; Berman, E; Mertens, E; Bouziri, N; Allali, Y; Helft, G; Lefeuvre, C; Isnard, R; Montalescot, G; Hammoudi, N
Abstract: Introduction: Mitral Valve Prolapse (MVP) is associated with complex ventricular arrythmia (VA) and sudden cardiac death but risk stratification remains unclear. Exercise induces an hyperadrenergic state and could trigger VA, however, data on exercise-induced VA (EIVA) in MVP patients are scarce. Objective: To describe EIVA prevalence, origin, characteristics and associated features in MVP patients. Methods: In this observational prospective study, 64 MVP asymptomatic patients (58±14 years, 41 men) with mild to severe mitral regurgitation (MR) and without left ventricular (LV) dysfunction, underwent echocardiography and symptom-limited exercise testing. Continuous 12-lead ECG monitoring was performed throughout testing. Severe EIVA was defined as ventricular triplets, sustained or non-sustained ventricular tachycardia (NSVT) or ventricular fibrillation. Results: All patients exercised at maximal intensity until exhaustion. EIVA was observed in 54 (84%) subjects including 12 (19%) patients with severe EIVA (7 triplets, 5 NSVT). Severe EIVA originated mainly from the mitral apparatus (all but one) and occurred at high exercise intensity (median 90% of predicted workload) or during early recovery phase. Compared to the rest of the cohort the patients with severe EIVA had similar resting ECG characteristics, similar LV dimension and function, similar degree of MR and mitral apparatus morphology. Finally, severe EIVA was not associated with an alteration of exercise tolerance. Conclusion: Exercise frequently unmasks ventricular arrythmia in patients with MVP. EIVA appears not linked to MVP features nor to exercise tolerance and seems to provide additional phenotyping information that could be linked to prognosis. Funding Acknowledgement: Type of funding sources: None.